2008
DOI: 10.1115/1.2903742
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Performance and Geometry of Supersonic Ejector

Abstract: The optimum geometries of the ejectors, which give maximum efficiency, are numerically predicted and experimentally measured. The numerical investigation is based on flow equations governing turbulent, compressible, two-dimensional, steady, time averaged, and boundary layer equations. These equations are iteratively solved using finite-difference method under the conditions of different flow regimes, which can be divided into several distinctive regions where the methods for estimating the mixing length are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…where Re is the particle's Reynolds number. The dynamic differential equation [24] of wheat seed in the stable accelerating zone III is expressed as the following equation:…”
Section: A Description Of Wheat Pneumatic Seeding Devicementioning
confidence: 99%
See 1 more Smart Citation
“…where Re is the particle's Reynolds number. The dynamic differential equation [24] of wheat seed in the stable accelerating zone III is expressed as the following equation:…”
Section: A Description Of Wheat Pneumatic Seeding Devicementioning
confidence: 99%
“…Using the equations (24) and (2)(3), the wheat speed and the actual steady airflow velocity were 56 m/s and 681 m/s for the optimized device, respectively. The actual steady airflow velocity was approximately 5.2% lower than the simulation result, and this result was consistent with the results reported by Wang (2009) [37]and Xu (2012) [38], which indicated that the simulation of the supersonic ejector flow field using the established model was reliable.…”
Section: Optimazation and Verification A Parameter Optimizationmentioning
confidence: 99%
“…The coal flow rate is metered using a digital scale and a stopwatch where the mass of the coal reservoir (29) is measured before and after each experiment. The detailed dimensions of the ejector and its convergent-divergent nozzle used in the experimental work are given in previous work of the corresponding author [11].…”
Section: Introductionmentioning
confidence: 99%
“…The present work outlines such a methodology, and identifies and discusses the optimum geometries for design and manufacturing of supersonic ejectors. Most studies reported ejector performance as a function of dimensional parameters (e.g., Hewedy et al [14], Kim and Kwon [15], Boumaraf and Lallemand [16], Li et al [17]). In this paper, an optimization technique is presented based on the three main geometrical values as dimensionless parameters.…”
Section: Introductionmentioning
confidence: 99%